Nutrient parameters limiting banana plant development in Vale do Ribeira, São Paulo State, Brazil - de Oliveira, Cibelle Tamiris; Rozane, Danilo Eduardo [UNESP]; de Lima Neto, Antonio João; Natale, William (FapUNIFESP (SciELO), 2024)
Vale do Ribeira is one of the largest banana producing regions in Brazil. However, information on soil fertility and nutrient status that could limit fruit production remains scarce. Thus, the present study diagnosed the most limiting nutrient parameters for the Nanica and Prata banana cultivars, in Vale do Ribeira, São Paulo State, based on soil and leaf chemical analyses. The data assessed included samples from commercial plantations in the municipalities of Eldorado, Cajati, Jacupiranga, Pariquera-açú, Registro and Sete Barras, between 2012 and 2020. The results of soil (pH, V, P, K, Ca, Mg, S, B, Cu, Fe, Mn and Zn) and leaf chemical analyses (N, P, K, Ca, Mg, S, B, Cu, Fe, Mn and Zn) were interpreted according to literature values and their maximums, minimums, means, coefficients of variation (CV), and confidence intervals (CI) were calculated at P < 0.05. Parameter classes were assessed according to their frequency distribution. A large part of the samples exhibited pH and V values similar to those recommended for banana plants. Although, average soil nutrient concentrations were considered high, soil K, Mg and S levels did not provide adequate banana plant nutrition, since these nutrients were deficient in the plants.
Parâmetros nutricionais limitantes ao desenvolvimento de bananeiras no Vale do Ribeira – SP
Keywords: leaf analysis; Musa spp; soil analysis; soil fertility